A6.9Distinct expression of T-cell homing molecules in human autoimmune lymph node stromal cells upon TLR-3 triggering - Haehnlein, J; Ramwadhdoebe, TH; Semmelink, J F; Choi, I Y; Smits, NAM; Berger, F H; Maas, M; Gerlag, D M; Geijtenbeek, TBH; Tak, P P; van Baarsen, LBM (Annals of the rheumatic diseases, 2015)
BackgroundRheumatoid arthritis (RA) is a prototypic autoimmune disease in which systemic autoimmunity precedes overt synovial tissue inflammation. The aetiology of RA is still unknown and systemic autoimmunity is probably initiated by an unidentified mechanism outside the synovium. Adaptive immune responses are generated in lymphoid tissue where the stromal compartment plays a crucial role in regulating T- and B-cell function. Murine studies have demonstrated that exposure to viral products can alter the interaction between lymph node stromal cells (LNSCs) and T-cells. However, little is known about the ability of human LNSCs to sense pathogens and their response to viral products. Viral infections have also been implicated the initiation and promotion of autoimmunity.ObjectiveHere we investigated which Toll-like receptors (TLRs) human LNSCs express and how TLR-3 triggering by polyI:C, affects gene and protein expression of human LNSC derived from lymph nodes obtained of healthy individuals and individuals with evidence of autoimmunity.Material and methodsWe included individuals with arthralgia who were positive for IgM rheumatoid factor and/or anti-citrullinated protein (n = 10; RA risk group), RA patients (n = 12) and healthy controls (HCs, n = 10). All subjects underwent ultrasound-guided inguinal lymph node biopsy and LNSCs were cultured directly from freshly collected biopsies. LNSCs of passage 3-6 were stimulated with polyI:C after which mRNA and protein levels were measured by qPCR, flow cytometry or ELISA.ResultsCultured human LNSCs expressed TLR1 to 9 with exception of TLR-8 mRNA and the strongest expression was observed for TLR-3. TLR-3 triggering in human LNSCs induced expression of adhesion molecules like VCAM-1 and ICAM-1 and inflammatory cytokines such as IL-6. In addition TLR-3 itself and type I IFN stimulated genes (ISGs) like IRF-7 and IP-10 were upregulated in response to polyI:C. For the ISG MxA we observed a significant lower induction in RA risk individuals compared with HCs (p = 0.0443). Strikingly, the expression of T-cell homing chemokines CCL19 and CCL20 was less induced upon TLR-3 triggering in LNSC obtained from RA risk individuals and RA patients compared with HCs. Likewise, we observed a lower induction of IL-8 protein production in LNSCs derived from RA patients compared with HCs (p = 0.0447).ConclusionsHuman LNSCs express different TLRs and are responsive to TLR-3 triggering. The observed lower induction in T-cell homing chemokines upon TLR-3 triggering in LNSC derived from RA risk individuals and RA patients could indicate a deregulation of antiviral responses in LNSC during autoimmunity.